On the numerical solution of differential-algebraic equations with index-3 - Guzel, Nuran; Bayram, Mustafa (ELSEVIER SCIENCE INC, 2006)
In this study, numerical solution of differential-algebraic equations (DAEs) with index-3 has been presented by Pade Approximation. An index reduction for differential-algebraic equation with index-3 is suggested. First index-3 system is reduced to index-1 system. Then we have applied the method for solving differential-algebraic equations with index-3 numerically. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: differential-algebraic equations (DAEs); index-3; Pade approximation; Mathematics